Marketing Communication Mix of Government of Rajasthan for Various Healthcare and Family Welfare Schemes: A Case Study of Western Rural Rajasthan - Kalla, Neelam (International Journal of Social Sciences and Management, 2016)
For a marketing professional both promotion and communications are essential. In fact, without effective marketing communications the consumer stay uninformed of products and services they need, which can be satisfying their needs and necessities competently. Past researches show that the key factor behind the failure to implement the schemes effectively is lack of awareness among the potential beneficiaries. In the present study research has undertaken an endeavor to analyze the prevailing means and channels of communication and investigate their effectiveness. The paper discusses the effectiveness of various communication channels, and agents operating in rural areas of western Rajasthan for government healthcare and welfare schemes. The paper also discusses the strategic interventions and the necessary changes based on results of study which need to be incorporated to enhance the effectiveness of communication mix of Government programs. Int. J. Soc. Sci. Manage. Vol-3, issue-2: 135-140